(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Stroke is one of the major causes of morbidity and mortality throughout the world, and carries greater economic costs. [MLC 601] originates from Traditional Chinese Medicine approved in 7 countries as drug that can aids post-stroke recovery. Objective:To assess [MLC 601] efficacy in improving outcomes of Iraqi patients’ stroke. Methods:Two hundreds ischemic stroke patients and 17 intracerebral hemorrhage patients were participated in this study; they took [MLC601] at the onset of their disease for 3 months and were assessed monthly for the motor power using modified Rankin scale mRs scale, speech, and visual field assessments. Results: mRs grade [4-5] were changed from (zero out of 159) at onset to (89 out of 55) at first month and to 98 out of 134 ischemic stroke patients after 3 months; also mRs grade [4-5] were changed from (1 out of 17) at onset to (12 out of 17) at first month and to 12 out of 17 intracerebral hemorrhage patients after 3 months. In 44% of the enrolled patients with aphasia were improved. Visual field assessments showed improvement in 43% of the patients with homonymous heminopia after 3 months [MLC 601] treatment. Conclusion:[MLC 601] is associated with improvement in all post stroke disabilities and placebo controlled trial is crucial to assess the benefit of it. Key worlds:Stroke, intracerebral hemorrhage, MLC 601, NeuroAid